TET2 Protects Against Vascular Smooth Muscle Cell Apoptosis and Intimal Thickening in Transplant Vasculopathy. Issue 6 (10th August 2021) - Ostriker, Allison C.; Xie, Yi; Chakraborty, Raja; Sizer, Ashley J.; Bai, Yalai; Ding, Min; Song, Wen-Liang; Huttner, Anita; Hwa, John; Martin, Kathleen A.
Abstract : Background: Coronary allograft vasculopathy (CAV) is a devastating sequela of heart transplant in which arterial intimal thickening limits coronary blood flow. There are currently no targeted therapies to prevent or reduce this pathology that leads to transplant failure. Vascular smooth muscle cell (VSMC) phenotypic plasticity is critical in CAV neointima formation. TET2 (TET methylcytosine dioxygenase 2) is an important epigenetic regulator of VSMC phenotype, but the role of TET2 in the progression of CAV is unknown. Methods: We assessed TET2 expression and activity in human CAV and renal transplant samples. We also used the sex-mismatched murine aortic graft model of graft arteriopathy (GA) in wild-type and inducible smooth muscle–specific Tet2 knockout mice; and in vitro studies in murine and human VSMCs using knockdown, overexpression, and transcriptomic approaches to assess the role of TET2 in VSMC responses to IFNγ (interferon γ), a cytokine elaborated by T cells that drives CAV progression. Results: In the present study, we found that TET2 expression and activity are negatively regulated in human CAV and renal transplant samples and in the murine aortic graft model of GA. IFNγ was sufficient to repress TET2 and induce an activated VSMC phenotype in vitro. TET2 depletion mimicked the effects of IFNγ, and TET2 overexpression rescued IFNγ-induced dedifferentiation. VSMC-specific TET2 depletion in aortic grafts, and in the femoral wire restenosis model, resulted in increased VSMC apoptosis and medial thinning. In GA, this apoptosis was tightly correlated with proliferation. In vitro, TET2-deficient VSMCs undergo apoptosis more readily in response to IFNγ and expressed a signature of increased susceptibility to extrinsic apoptotic signaling. Enhancing TET2 enzymatic activity with high-dose ascorbic acid rescued the effect of GA-induced VSMC apoptosis and intimal thickening in a TET2-dependent manner. Conclusions: TET2 is repressed in CAV and GA, likely mediated by IFNγ. TET2 serves to protect VSMCs from apoptosis in the context of transplant vasculopathy or IFNγ stimulation. Promoting TET2 activity in vivo with systemic ascorbic acid reduces VSMC apoptosis and intimal thickening. These data suggest that promoting TET2 activity in CAV may be an effective strategy for limiting CAV progression. Abstract : Supplemental Digital Content is available in the text.